Teacher's Perspective on the Management Team at the Islamic Boarding School - Siti Alsyah; Inom Nasution; Rusydi Ananda (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The background of the research arises from the need for pesantren institutions to build an effective educational governance system thru the role of institution managers who can direct program implementation. This is because the policy-making process in many educational institutions is still dominated by the main leadership, leaving little room for educators to engage in management functions and institutional decision-making. Teachers' assessments of the management of the pesantren influence the work atmosphere and discipline, so this research examines teachers' opinions on the tasks and composition of the management team, then reviews the communication process, decision-making factors that affect teachers' views, and their impact on the pesantren environment. Thru interviews, observations, and documentation, the researcher collected data from the principal, vise principal, administrative staff, and teachers at the Al-Kautsar Al-Akbar Modern Islamic Boarding School. A qualitative phenomenological approach was chosen to understand the experiences and views of teachers regarding the management of the boarding school, and the findings were analyzed to identify patterns emerging from each piece of information obtained. The research results show that the pesantren already has a fairly organized division of management tasks, although some decisions are still largely determined by the leadership. Meanwhile, the communication relationship between the managers and teachers is open, both thru meetings and digital media. Decision-making is carried out thru deliberation, although teachers more often provide suggestions. The way teachers view management is influenced by work relationships, communication patterns, pesantren culture, and their involvement in management. Additionally, the positive views of the teachers contribute to a comfortable work atmosphere, enhance discipline, and foster responsibility and professionalism in the pesantren.